PENGARUH PERCEIVED ORGANIZATIONAL CAREER MANAGEMENT TERHADAP KEPUASAN KARIR DENGAN ADAPTABILITAS KARIR SEBAGAI PEMODERASI PADA PEGAWAI NEGERI SIPIL PEMKO BANDA ACEH - Nadya Turrahmi; Lenny Rakhmawati (Departemen Manajemen, 2020)
ABSTRACT:This research aims to determine the influence of perceived organizational career management and career adaptability to the career satisfaction of civil servants in Banda Aceh and the influence of career adaptability in moderate perceived organizational career management on the satisfaction of civil servants in Banda Aceh. The population in this research is the civil servants of Pemko Banda Aceh with a total of 1,335 employees who have subsequently withdrawn as many as 297 employees as a sample. By using the data analysis method hierarchical linear model. The results showed that perceived organizational career management affected career satisfaction. Career adaptability affects the career satisfaction of civil servants in Banda Aceh. This proves that career adaptability is one of the individual's readiness to confront obstacles in career transition conditions. And career adaptability moderates the influence of perceived organizational career management towards the career satisfaction of civil servants in Banda Aceh.